Russia’s legal narratives for the war on Ukraine: a political analysis of motivations, geopolitical dynamics, and international responses - Fayad, Ghinwa (2025)
This thesis examines how Vladimir Putin and Russian political elites have intentionally reinterpreted and manipulated international legal norms to justify Russia’s attack on Ukraine in February 2022. The main contribution of this study is to show that Russia’s legal narratives are not just rhetorical devices but part of a broader strategic maneuver, framing its actions as legitimate under the principles of self-defense, right to self- determination and the protection of nationals. These narratives seek to both challenge the Western-dominated international legal order, and advancing Russia’s geopolitical goals at the same time, while maintaining regional influence, countering NATO expansion, and consolidating domestic power. Through an extensive analysis of Russia’s legal arguments and their structural employment, the thesis demonstrates how Russia exploits ambiguities within international law to establish new realities, especially with the recognition of breakaway regions like the Donetsk and Luhansk. It also explores the international reception of these narratives highlighting the division between Western states that rejects Russia’s claims, and some countries in the global South that adopt neutral positions. The findings of this thesis show that Russia’s manipulation of international law risks destroying key legal principles such as sovereignty, territorial integrity, and non-intervention, which, in turn fragment global governance norms. Ultimately, this thesis argues that the strategic use of legal narratives by Russia indicates a broader shift toward a multipolar interpretation of international law. This evolution challenges the unity and resilience of the international legal order while raising critical questions about its capacity to limit big power behavior in a contested world.